Comparisons of nonpharmaceutical analgesia and pharmaceutical analgesia on the labor analgesia effect of parturient women - Rongyu Zhu; Qin Pan; Xiaoxia Cao (Immunity, Inflammation and Disease)
Abstract Objective We aimed to compare the labor analgesia effects of nonpharmaceutical analgesia and pharmaceutical analgesia on parturient women. Methods One hundred and four parturient women with spontaneous births were selected and randomly divided into pharmaceutical and nonpharmaceutical analgesia groups. Before and after analgesia, the Visual Analogue Scale (VAS), parturient satisfaction with analgesia, serum pain stress factors (substance P [SP], neuropeptide Y [NPY], nerve growth factor [NGF], and prostaglandin E2 [PGE2]), duration of labor, vaginal bleeding at 2 h postpartum, postpartum urinary retention and dysuria incidence, Apgar score of 1 min and 5 min after birth, and neonatal cord blood gas analysis (pH, partial pressure of oxygen [PO2], partial pressure of carbon dioxide [PCO2], and lactate [Lac]) were compared in the two groups. Results VAS scores were lower and the analgesia satisfaction was higher in the pharmaceutical analgesia group than in the nonpharmaceutical analgesia group (all p < .05). Serum levels of SP, NPY, NGF, and PGE2 in the pharmaceutical analgesia group were lower than those in the nonpharmaceutical analgesia group (all p < .05). The first and second stages of labor were longer and the bleeding volume at 2 h postpartum was greater in the pharmaceutical analgesia group than those in the nonpharmaceutical analgesia group (all p < .05). Reduced Lac and PCO2 levels and increased PO2 level were found in the pharmaceutical analgesia group in comparison to the nonpharmaceutical analgesia group (all p < .05). Conclusion This study demonstrates that the analgesic effect and neonatal condition of the pharmaceutical analgesia are better than the nonpharmaceutical analgesia, but the labor duration and postpartum bleeding volume of the pharmaceutical analgesia are greater than those of the nonpharmaceutical analgesia.